Perceived burden of care and reported coping strategies and needs for family caregivers of people with mental disorders in Zimbabwe - Bazondlile D. Marimbe; Frances Cowan; Lazarus Kajawu; Florence Muchirahondo; Crick Lund (African Journal of Disability, 2016)
Background: Mental health service resources are inadequate in low-income countries, and families are frequently expected to provide care for their relative with a mental disorder. However, research on the consequences of care giving has been limited in low-income countries, including Zimbabwe. Objective: The study explored the perceived impact of mental illness, reported coping strategies and reported needs of family members of persons diagnosed with bipolar affective disorder or schizophrenia attending a psychiatric hospital in Harare, Zimbabwe. Methods: A purposive sample of 31 family members participated in in-depth interviews and focus group discussions using standardized study guides. Participants were also screened for Common Mental Disorders (CMD) using the 14-item Shona Symptom questionnaire (SSQ). Qualitative data were analyzed thematically. Statistical Package for Social Sciences (SPSS version 16) was used for quantitative data analysis. Results: Caregivers experienced physical, psychological, emotional, social and financial burden associated with care giving. They used both emotion-focused and problem-focused coping strategies depending on the ill family members’ behaviours. Seeking spiritual assistance emerged as their most common way of coping. Twenty one (68%) of the caregivers were at risk of CMD and were referred to a psychiatrist for further management. Caregivers required support from health care professionals to help them cope better. Conclusion: Caregivers carry a substantial and frequently unrecognized burden of caring for a family member with mental disorder. Better support is needed from health professionals and social services to help them cope better. Further research is required to quantitatively measure caregiver burden and evaluate potential interventions in Zimbabwe.